2012
DOI: 10.1136/bjophthalmol-2012-301580
|View full text |Cite
|
Sign up to set email alerts
|

Lid-parallel conjunctival folds (LIPCOF) and dry eye: a multicentre study

Abstract: The displayed medium sensitivity and specificity, and good positive predictive value of the LIPCOF test support the use of LIPCOF grading as a simple, quick and non-invasive dry eye screening tool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 19 publications
1
29
0
4
Order By: Relevance
“…A possible reason for these results may be that when MGD occurred, the changes of lipid composition and quantity would affect the stability of tear film, causing the decline of BUT. Research [11] showed that there was significant correlation between conjunctivochalasis and MGD, that is, the heavier the degree of conjunctivochalasis, the higher the incidence of MGD. As for the negative results on tear film fragment, tear film foam, upper and lower tear meniscus height, and corneal fluorescein staining, previous studies indicate that there might be some correlation between these signs and the severity of dry eye symptoms [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A possible reason for these results may be that when MGD occurred, the changes of lipid composition and quantity would affect the stability of tear film, causing the decline of BUT. Research [11] showed that there was significant correlation between conjunctivochalasis and MGD, that is, the heavier the degree of conjunctivochalasis, the higher the incidence of MGD. As for the negative results on tear film fragment, tear film foam, upper and lower tear meniscus height, and corneal fluorescein staining, previous studies indicate that there might be some correlation between these signs and the severity of dry eye symptoms [16].…”
Section: Discussionmentioning
confidence: 99%
“…according to Institute for Eye Research (IER), conjunctival congestion was graded as 0 (no congestion), 1 (congestion was confined to the fornix and blood vessel was bright red), 2 (congestion was obvious and reached to palpebral fissure and blood vessel was crimson and fuzzy), or 3 (congestion was diffuse, blood vessel was fuchsia, and meibomian gland texture was not clear); according to LIPCOF (Lid-parallel conjunctival folds) [11, 12], conjunctivochalasis was graded as 0 (no obvious fold), 1 (single fold), 2 (2 folds, but the height of the fold was lower than the height of tear film), or 3 (many folds, and the height of the fold was higher than the height of tear film). …”
Section: Methodsmentioning
confidence: 99%
“…Bulbar and limbal hyperaemia can give an indication of ocular surface health and more recently the degree of both lid parallel conjunctival folding (LIPCOF) and lid wiper epitheliopathy (LWE) have been added to the list of potential indicators of dry eye. [5][6] [7] LIPCOF graded at least grade 2 is likely to be associated with dry eye symptoms [8].…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the Presence and Absence of Lid-Wiper Epitheliopathy in Contact Lens Wearersstress caused by rubbing [18][19][20]. Among those, Pult et al18 reported that nasal LIPCOF was related to dry eye symptoms.…”
mentioning
confidence: 98%